Bond Degradation between Deformed Reinforcement and Concrete under Variable Repeated Loads - CHENG Hongyuan; MA Jinyao; ZHENG Dan; CHENGWEN Baihe; LI Xinxin (Renmin Zhujiang)
The bond-slip constitutive model between reinforcement and concrete under repeated loads is an important basis for the assessment of the overall performance of reinforced concrete structures and reinforcement repair after earthquakes. Since the bond stress is mainly composed of the mechanical occlusion force between deformed reinforcement and concrete, the lateral confinement state in the bond region will affect its bond performance. On this basis, this paper investigated the effect of variable repeated loads under lateral pressure on the bond performance between reinforcement and concrete, quantitatively analyzed the degradation law of bond parameters with variable repeated loads, and studied the bond damage mechanism between reinforcement and concrete by using digital image technology. It is shown that under the condition of sufficiently restrained concrete protective layer, the bond degradation between reinforcement and concrete is mainly related to the displacement controlled by repeated loads, while the effect of lateral pressure on it is negligible.